(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Although the Irish seabed extension holds potential for wave energy in accelerating the energy transition, one of the largest roadblocks in upscaling these technologies arises from the lack of technology readiness, i.e. no single technology design is cost-competitive enough to make its way into commercial take-off. Often considered the domain of other specialists such as marketers, commercialisation is the least developed area of innovation management. While the management literature argues that technology development shifts toward up-scaling and mass commercialisation after the market is formed, little emphasis is given to the transition process where a technology trajectory becomes a standard in the industry as it converges in a fully developed dominant design. By establishing industry guidelines, standards can have simultaneously contradictory and complementary effects on innovation activity. Standards define the interfaces used for product communication, allowing for interoperability and reducing technological uncertainties, which can enable the scaling up of production. Their use is linked to ensuring compatibility between systems, reducing costs, and encouraging large-scale adoption of renewable technologies. In a world of constant technological change and variation, the industry needs to signal to investors what technology components and aspects are worth investing in. In energy technologies’ life-cycle, technology standards often formalise sought-after industry dominant designs, incentivising other actors to imitate, and follow-on technologies to increment upon the dominant design rather than to ferment new paradigms. While energy technologies are essentially complex and technological widespread diffusion is slow, they tend to give rise to a self-reinforcing process that becomes entrenched in innovation, usually a dominant technology paradigm. This study explores how technology standards and dominant designs can advance emerging technologies, considering the context of offshore renewable energy technologies, especially wave energy in Ireland. Our preliminary findings suggest that, although approached as the same in some papers, not every technology standard can be understood as a dominant design. Both technology standards and dominant designs can, through their potential in reducing technology variety and orienting the technology trajectory, allow for industry convergence and enable economies of scale. However, they essentially differ on their way of emergence, evolution and their effects on innovation activities. Besides technology-level factors, a comprehensive review laid out the importance of exploring windows of opportunities on the firm-level, considering firms’ access to resources and capabilities. Literature also highlights the role of governments as central in supporting the deployment of renewable energy when market demand is insufficient – as happened in the solar case – as well as their potential to explore standards in order to promote technology innovation. This study contributes to a literature gap on better understanding the role of technology standards and dominant designs in upscaling emerging technologies. It also emphasises that understanding how technology standardisation occurs can help better comprehend the emergence of dominant designs, using technology standards as a pre-hoc tool for designs that can only be identified post-hoc, and ultimately furthering the discourse of accelerating energy innovation in a stagnant industry such as wave.